Analysis of the causes of admission to the University Children’s Hospital of Lublin in 2004-2006 - Kucmin, Tomasz; Chemperek, Ewa; Płowaś-Goral, Małgorzata; Krawczyk, Wojciech; Szwarc, Paweł; Nogalski, Adam (Polish Journal of Public Health, 2010)
Aim. The aim of the study was to evaluate the reasons for admission to the University Children’s Hospital of Lublin in 2004-2006.Material and methods. Data from the Children’s Hospital Emergency Department were analyzed and consequently seven main reasons for admission were identified: surgical illnesses, traumas, burns, road traffic accidents, pediatric illnesses, otolaryngological illnesses and poisoning.Results. The main reasons for admission were pediatric illnesses that accounted for 47.9% of all admissions. The second most frequent cause of admission was trauma (23.1%), and the prevalence of other causes was the following: surgical illnesses (14.5%), otolaryngological illnesses (7.9%), poisonings (2.7%), burns (2.1%) and road traffic accidents (1.8%). The average number of hospitalizations within 24-hour periods was the highest on first weekdays and the lowest on weekends. During the first 6 months of each year the number of admissions due to surgical illnesses was the highest. Each year between April and September the main cause of admission was trauma, and during autumn and winter children with pediatric and otolaryngological illnesses were hospitalized most frequently.